Sarcoglottis wernerherzogii (Spiranthinae) : a new species from Cusco, Peru - Collantes Meza, Benjamín
A new species of Sarcoglottis from the department of Cusco, Peru is described and illustrated as S. wernerherzogii. It is similar to eastern South American S. fasciculata but distinguished by its contrasting habitat (high-Andean montane cloud forest as 2050−2500 m a.s.l. vs. Atlantic rain forest near sea level), flowering after the shed-ding of the leaves (vs. flowering with leaves present); homogeneous green or yellow flowers (vs. whitish or pale green with contrasting reddish veins); rigidly conduplicate-concave lateral sepals that, when spread out are strongly falcate (vs. slightly concave, not rigid, obliquely lanceolate lateral sepals); strongly cymbiform, obovate hypochile as wide as long when spread out (vs. broadly channeled, oblanceolate hypochile about twice longer than wide or longer when spread out); ovate, strongly deflexed epichile provided with a central longitudinal thickening throughout its length (vs.erect or gently arcuate epichile with a thickening only at the apex); and apical anther beak truncate (vs. apical anther beak rounded). The strongly cymbiform hypochile that, when spread out is as wide as long, is unique in the genus. The differences between S. fasciculata, the new species, and other Peruvian species of Sarcoglottis are contrasted in a table. Sarcoglottis wernerherzogii is known from less than a dozen plants in two populations, both under nominal protection in the Machupicchu Historical Sanctuary and the Area of Conservación Regional Choquequirao, respectively. The status "DD" (data deficient) is suggested until an objective assessment of its risk status can be carried out.